A Call for Strengthening the Role of Comparative Legal Analysis in the United States - CALBOLI, Irene (Institutional Knowledge at Singapore Management University, 2017)
This Essay highlights the importance of comparative legal analysis with particular emphasis on the role that this methodology could play for intellectual property scholarship in the United States. In particular, the theme of this Symposium aims at addressing “values,” “questions,” and “methods” in intellectual property law. In line with this theme, this Essay would like to make the case that comparative legal analysis could play a more prominent role as a scholarly methodology in the U.S. legal academy in the field of intellectual property. In turn, this could have a relevant impact on the questions addressed by scholars and provide the opportunity for broader—or partially different—answers. Thus, comparative analysis can enrich the discussion over the values to be promoted or protected as part of the intellectual property debate in the U.S. In other words, this Essay suggests that U.S. scholars could consider turning with more frequency to comparative legal analysis as an additional methodology to use in their research.